The Contribution of Supervisory Support to Employee Job Satisfaction at the Social Services Office of Padang City - Prayitno, Afifah Putri; Zulian Fikry (Causalita, 2024)
Employees are a valuable asset and an essential component of an organization, contributing to the organization’s image. The relationship between employees and their supervisors is ongoing and continuous. This study is a quantitative research aimed at examining the Contribution of Supervisor Support to Job Satisfaction among employees at the Social Services Department of Padang City. The respondents of this study consisted of 59 employees from the Social Services Department in Padang City, selected using purposive sampling. Data was analyzed using simple regression analysis and collected through a questionnaire containing Likert-scale items related to supervisor support and job satisfaction variables. The results of the simple regression analysis indicate a significant positive contribution of supervisor support to employee job satisfaction, with a significance level of 0.023 (p < 0.05). Supervisor support, which includes assistance, listening, and care, plays a role in creating a conducive work environment for employees. These findings align with previous research showing that supervisor support can enhance job satisfaction through employee well-being and motivation. In conclusion, adequate supervisor support can improve employee job satisfaction, which ultimately contributes positively to organizational performance.